(untitled) (Journal of Global Accounting, 2023)
The research investigated business adaptability, sustainability, and long-term survival in a disruptive organisational environment. The study’s overarching purpose was to explore the moderating influence of disruptive organisation environment on the link between corporate agility and organisational performance of manufacturing companies in the state of Rivers. The reaction of correspondents in the state of Rivers was analysed via questionnaire. After calculating the Mean and Standard Error of the Mean, the compiled responses were evaluated using coefficient determination, ANOVA, and regression analysis. Corporate agility has no significant relationship with the organisational performance of manufacturing organisations in the state of Rivers (t-test = 0.14, p-value = 0.989>0.05); the moderating effect of a disruptive organisation environment on corporate agility has no significant effect on organisational performance (F-ratio = 0.76, p-value = 0.469>0.05). Based on this conclusion, the study suggests that organisational performance in the Nigerian state of Rivers is unaffected by corporate agility and a somewhat disruptive organisational environment. In order to increase investment prospects and organisational performance of industrial organisations in Nigeria’s Rivers state, the research recommends a reduction in operating costs, consistent investment-friendly government regulations, and efficient infrastructure facilities.